2011
DOI: 10.1210/en.2011-0109
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Growth Arrest and DNA-Damage-Inducible Gene β (GADD45β) as a Novel Tumor Suppressor in Pituitary Gonadotrope Tumors

Abstract: Gonadotrope and null cell pituitary tumors cause significant morbidity, often presenting with signs of hypogonadism together with visual disturbances due to mass effects. Surgery and radiation are the only therapeutic options to date. To identify dysregulated genes and pathways that may play a role in tumorigenesis and/or progression, molecular profiling was performed on 14 gonadotrope tumors, with nine normal human pituitaries obtained at autopsy serving as controls. Bioinformatic analysis identified putative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 40 publications
5
86
0
5
Order By: Relevance
“…IGSF1 expression was observed in thyrotropes, somatotropes, and lactotropes, but not gonadotropes (Sun et al 2012), which is consistent with our results in the adult rat. However, increased amounts of Igsf1 mRNA have been observed in pituitary adenoma secreting GH or prolactin, while decreased amounts were observed in those secreting ACTH or gonadotropins (NCBI GEO profiles ID 11104016 (Morris et al 2005), 83167537 (Michaelis et al 2011)), in accordance with the PIT1 lineage.…”
Section: Figurementioning
confidence: 99%
“…IGSF1 expression was observed in thyrotropes, somatotropes, and lactotropes, but not gonadotropes (Sun et al 2012), which is consistent with our results in the adult rat. However, increased amounts of Igsf1 mRNA have been observed in pituitary adenoma secreting GH or prolactin, while decreased amounts were observed in those secreting ACTH or gonadotropins (NCBI GEO profiles ID 11104016 (Morris et al 2005), 83167537 (Michaelis et al 2011)), in accordance with the PIT1 lineage.…”
Section: Figurementioning
confidence: 99%
“…Mi cha e lis ir au to riai nu sta të, kad GADD45a eks pre si ja be veik ne si sky rë svei kø ir ser ganèiø HA or ga niz muo se, o GADD45b eks pre si ja, ser gant ðiuo na vi ku, bu vo su ma þë ju si. Ta èiau pro mo to riaus me ti -li ni mas ne bu vo ap tik tas, tai gi prie þas tis lie ka ne aið ki [35].…”
Section: Sporadinës Haunclassified
“…P53 yra ga lin gas transk rip ci jos fakto rius, re gu liuo jan tis tu mo ro su pre so riø ge nø funk ci jas, pa vyz dþiui, DNR re pa ra ci jà, làs te lës cik lo ir da li ni mo si stab dy mà, se në ji mà ir apop to zae [23]. TP53 yra vie nas labiau siai inak ty vuo ja mø ge nø ávai riø na vi kø pa to genezëje, ta èiau HA at ve ju tai ste bi ma re tai, daþ niau jas su kelia p53 kas ka do je da ly vau jan tys ge nai ir jø pro duk tai [23,35].…”
Section: Sporadinës Haunclassified
“…With the exception of GADD45g (GADD45G), characterised by Zhang et al (70), the functional involvement of the majority of these genes in pituitary tumour pathogenesis remains to be determined. Indeed, GADD45 (GADD45A) expression has been extensively studied by independent groups (70,71,72,73); all of which demonstrated that the down-regulation of GADD45g is more frequently found in non-functioning pituitary adenomas (NFPAs) than in functioning tumours (90 and 58% respectively) ((74, 75) for review), and that promoter methylation seems to be the major cause of loss of GADD45 expression in pituitary tumours (71).…”
Section: Gene Expression By Transcriptome Analysesmentioning
confidence: 99%